Habitat Use by Brood-Rearing Waterfowl in Subarctic Québec - Décarie, Robert; Morneau, François; Lambert, Daniel; Carrière, Suzanne; Savard, Jean-Pierre L. (ARCTIC, 1995)
Aerial surveys of waterfowl were conducted in subarctic Quebec in 1989 and 1990 on randomly selected 100 sq km plots. We used logistic regression for modelling relationships betweren the presence of waterfowl broods and habitat characteristics. For each species, models of habitat use were generated with one data set and tested with two others. We also compared the frequency distributions of broods of each species in different habitat types. Correct-classification rates of models varied betweren 0.53 and 0.77. Sensitivity of models generally increased when applied to validation data sets. Models showed that green-winged teals (Anas crecca) avoided lakes >501 ha and used vegetated lakes, ponds and fens or bogs more than predicted by their availability. Black scoters (Melanitta nigra) and surf scoters (M. perspicillata) were found mostly on small lakes (<10 ha) and medium lakes (10-100 ha). Black scoters were associated with the presence of ponds and lakes with sedge and grass, whereas surf scoters were not. The presence of scaup (Aythia spp.) broods was associated with the presence of vegetation. Green-winged teals were observed more often on bogs than were either scoters or scaups. Black scoters were observed more often on ponds and less often on medium-sized lakes than surf scoters and scaups. The latter differed in their use of lakes <10 ha: surf scoters, like black scoters, mostly used unvegetated lakes, while scaups and green-winged teals mostly used vegetated lakes. The accuracy and precision of logistic models may be enhanced by additional habitat variables, careful selection of sample-cell size and further investigation of the breeding biology of the surveyed species.Key words: habitat, model, logistic regression, northern Québec, black scoter, surf scoter, green-winged teal, scaup, brood Des inventaires aériens de sauvagine dans des parcelles de 100 km² sélectionnées aléatoirement ont été réalisés dans le Québec subarctique en 1989 et en 1990. La régression logistique fut utilisée pour ...